Food Security in Less Developed Countries, 1970 to 1990 - Jenkins, J. Craig; Scanlan, Stephen J. (American Sociological Review, 2001)
Despite a global food surplus, almost half of the world's less developed countries suffer significant problems concerning food. Most social science and policy discussions of food security make the “food availability” assumption that increased food supply is the key to reducing hunger. Critics argue, however, that increased food supply has little impact on hunger and that the primary culprits are entrenched inequality and militarism. A lagged panel analysis of food supply and child hunger rates (1970–1990) shows that the food supply has only modest effects on child hunger rates and that food supply is structurally rooted in development processes (domestic investment, urban bias, foreign capital penetration) while child hunger is politically based in arms imports, internal violence and political democratization. Population pressure, tapped by increased age dependency, undermines both the supply of food and the population's access to it, and cultural dualism magnifies the effects of population pressure on child hunger. The effects of economic growth “trickle down” to affect both food supply and child hunger, and economic growth is also positively correlated with political democratization, suggesting there is no short-term “trade-off” between growth, democratization, and social equity.